Cationic vacancies and anomalous spectral-weight transfer in Ti 1-xTaxO2 thin films studied via polarization-dependent near-edge x-ray absorption fine structure spectroscopy - Qi, D.-C. (2014)
10.1103/PhysRevB.87.245201